KESESUAIAN PENYIMPANAN OBAT HIGH ALERT DI INSTALASI FARMASI RUMAH SAKIT X BANJARMASIN - Ilahi, Fitrah Shafran; Rahmah; Yumassik, Abdul Mahmud; Nordin; Ainah, Nur; Istiqamah, Farida; Faqih, Muhammad (Jurnal Insan Farmasi Indonesia, 2025)
High Alert is a type of drug that needs to be taken seriously as it can often lead to fatal errors and also has a high potential to trigger Adverse Drug Reactions. These drugs are divided into three categories, namely High Risk drugs, High Concentrate Electrolytes, and Look Alike Sound Alike/ Drug Name Look and Sound Similar. The purpose of this study was to assess the suitability of High Alert drug storage at the Banjarmasin X Hospital Pharmacy Installation based on the standard operating procedure for High Alert drug storage. The research method used qualitative observational with a cross-sectional approach. The study sample included 158 items of High Alert drugs in the Pharmacy Warehouse, Outpatient Pharmacy Depot, and Inpatient Pharmacy Depot, taken using the Total Sampling technique and data collected prospectively using a checklist sheet. Then processed with Microsoft Excel based on standard operating procedures. The results showed that the suitability of High Alert drug storage in the Pharmacy Warehouse was 99% (61 items), Outpatient Pharmacy Depot was 100% (41 items), and Inpatient Pharmacy Depot was 98% (51 items). Overall, the average suitability of High Alert drug storage in the three depots is 99% suitable in drug storage.